Practices & attitudes towards recovery in elite Asian & UK adolescent athletes - Murray, A. M.; Turner, A. P.; Sproule, J.; Cardinale, M. (Physical Therapy in Sport, 2017)
Objectives: Assess current practice and attitudes towards recovery in adolescent athletes. Design: Questionnaires were administered either via print or online questionnaire. Participants: Athletes and coaches from within Asia were surveyed (n = 112 & 53), with a comparative sample in the UK (n = 53 & 8). Main outcome measures: The approaches and attitudes to recovery in both training and competition. Results: Adolescent athletes perceive a variety of recovery modalities as important, though prioritise active recovery, nutrition and sleep. Attitudes towards recovery differed between athletes in Asia and the UK with respect to the perceived benefits of: sleep (96% believe in it in the UK v 69% in Asia, p < 0.01); nutrition (92 v 58%, p < 0.01); and active recovery (70 v 52%, p = 0.03). The number of recovery techniques used with Asian athletes was higher after training (p = 0.009) and competition (p < 0.01). Asian athletes rely more on `feel` to justify interventions. Conclusions: There was a major disconnect amongst athletes` belief in particular strategies and their behaviours. The results of this study show the need for educating coaches and athletes.